(untitled) (Mugda Medical College Journal, 2026)
Dengue is a significant public health concern in numerous tropical and subtropical nations like Bangladesh, especially in industrial and semi-urban regions, which have witnessed the majority of outbreaks. An estimated 50 million dengue infections occur worldwide annually and it has been included among the top ten global health hazards by the World Health Organization. Humans are among the only known hosts for the dengue virus, which is spread by the Aedes mosquito. In Bangladesh, the prevalence of dengue has experienced a substantial rise over the past 35 years, with growing urbanization, modernization, and global warming being widely regarded as the primary drivers. Factors like rapid urbanization, unchecked population growth, failing waste management systems, and absence of effective vector control contributed to the rise and spread of dengue infection in the country. This review paper aims to thoroughly examine the dynamics of dengue infection, with a focus on the interrelated impacts of climate, urbanization, and public health preparedness in Bangladesh. The approach entails analyzing past viewpoints, changes in population, and factors that influence society, while also evaluating government policies, ethical concerns, and initiatives sponsored by the community. The review will try to discover effective techniques for dengue prevention and control by examining successful community development initiatives and behaviour change models. Mugda Med Coll J. 2026; 9(1): 73-80